Pulmonary Actinomycosis in a Male Patient with a Tracheal Bronchus - Cecilia T Costiniuk; Nha Voduc; Carolina de Souza (Canadian Respiratory Journal)
BACKGROUND: Tracheal bronchus is a congenital malformation comprising an abnormal bronchus originating from the trachea or other bronchus. This malformation has been associated with recurrent pneumonia in children, but is rarely associated with infection in adults. Actinomyces species are rare causes of necrotizing pneumonias that often masquerade as malignancy, lung abscesses and tuberculosis.